Hubungan Antara Perilaku Wajib Pajak dan Kebijakan Pajak Berdasarkan Sudut Pandang Behavioral Accounting - Widyaningtyas, Nina Septika (E-Jurnal Akuntansi; Vol 30 No 1 (2020), 2020)
This study aims to examine and describe the relationship between taxpayer behavior and tax policy based on a behavioral accounting perspective. The used research approach is a qualitative approach by using collected secondary data from using literature studies. Data analysis uses qualitative techniques by studying research data, interpreting and taking conclusions. The results of the study stated that the factors, which influence taxpayer compliance behavior can be divided into two, namely internal and external factors. Internal factors are factors that originate from within the taxpayer, which can be in the form of a taxpayer's trust in the government and the taxpayer's law and knowledge of tax regulations. External factors are factors originating from outside the taxpayer themselves, which can be in the form of fair and clear tax sanctions and the implementation of tax socialization by the tax authority. The research results also stated that increasing taxpayer compliance needs to be the target of government tax policy in order to state tax revenue run optimally. Keywords :Taxpayer Behavior, Tax Policy, Behavioral Accounting